Cranial characters in Caiman crocodilus (Crocodylia: Alligatoridae) with emphasis on the subspecies distributed in Colombia - Falcón Espitia, Nelson (2021)
Studies on the biology of Caiman crocodilus have drawn attention to its biology with emphasis on systematic, taxonomy and ecology. However, anatomical aspects, such as skull characteristics, have not been studied in detail throughout its geographic range. In this study the skull characteristics for C. crocodilus subspecies, C. c. fuscus, C. c. chiapasius, C. c. crocodilus, and C. c. apaporiensis were analyzed using geometric morphometrics and descriptive morphology, including geographic and ontogenetic variation. Variation in skull morphology was found between the subspecies analyzed. Trans-Andean subspecies, C. c. fuscus and C. c. chiapasius, exhibit brevirostrine skulls but they are different in the contact between frontal and nasal bones and the size of the palatine process of the maxilla; therefore, populations in Colombia correspond to C. c. fuscus and, C. c. chiapasus is not distributed in Colombia. Although cis-Andean subspecies, C. c. apaporiensis and C. c. crocodilus, have longirostrine skulls, both subspecies differ in the shape of the skull and in osteological characters; then, adults of C. c. apaporiensis present frontal and nasal in contact and, V-shape maxillary-premaxillary suture; while C. c. crocodilus specimens exhibit a high geographic and ontogenetic variation, supporting the hypotheses that there at least two clades of such subspecies for Colombia. These morphological differences should be considered in future systematics studies and policies on global conservation of the different C. crocodilus subspecies.